2017
DOI: 10.1063/1.4999046
|View full text |Cite
|
Sign up to set email alerts
|

On the dissipation and dispersion of entropy waves in heat transferring channel flows

Abstract: This paper investigates the hydrodynamic and heat transfer effects upon the dissipation and dispersion of entropy waves in non-reactive flows. These waves, as advected density inhomogeneities downstream of unsteady flames, may decay partially or totally before reaching the exit nozzle, where they are converted into sound. Attenuation of entropy waves dominates the significance of the subsequent acoustic noise generation.Yet, the extent of this decay process is currently a matter of contention and the pertinent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 44 publications
11
59
0
Order By: Relevance
“…Further, as the wave spreads out the spectral distribution of the entropy wave becomes limited to the low frequency regions. It has already been shown that low frequency components of the entropy wave can survive turbulent flow much better than those of high frequencies (Fattahi et al 2017). Thus, the contribution of turbulent mixing to the overall diffusion process is progressively hindered as the wave thickens and molecular diffusion becomes the dominant diffusion mechanism.…”
Section: Entropy Wave Advectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, as the wave spreads out the spectral distribution of the entropy wave becomes limited to the low frequency regions. It has already been shown that low frequency components of the entropy wave can survive turbulent flow much better than those of high frequencies (Fattahi et al 2017). Thus, the contribution of turbulent mixing to the overall diffusion process is progressively hindered as the wave thickens and molecular diffusion becomes the dominant diffusion mechanism.…”
Section: Entropy Wave Advectionmentioning
confidence: 99%
“…This was achieved in a setup with long wavelength entropy waves and an isothermal base flow. However, more recent numerical simulations of heat transferring flows revealed that advective entropy waves in channels could significantly deviate from being one-dimensional fronts (Fattahi et al 2017). Studies on the conversion of entropy waves to sound in turbine stages (Cumpsty & Marble 1977; 2013; Livebardon et al 2016) have supplied their models with realistic entropy waves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eckstein & Sattelmayer 2006;Schulz et al 2019) and with their measurements (Wassmer et al 2017;De Domenico et al 2019). Most of the modelling efforts to date have been about entropy-wave dispersion in fully developed turbulent duct flows (Sattelmayer 2002;Morgans, Goh & Dahan 2013;Morgans & Duran 2016;Giusti et al 2017;Fattahi, Hosseinalipour & Karimi 2017;Christodoulou et al 2020;Hosseinalipour et al 2020), where shear dispersion was identified as the dominant mechanism. There are indeed several mechanisms at play that contribute to the decay of entropy waves (e.g.…”
Section: Introductionmentioning
confidence: 99%